74TiPPhase I study of BI 836880, a VEGF/Ang2-blocking nanobody®, as monotherapy and in combination with BI 754091, an anti-PD-1 antibody, in Japanese patients (pts) with advanced solid tumours. (24th November 2019) - Yamazaki, K; Koyama, T; Shimizu, T; Takahashi, T; Watanabe, J; Tanaka, Y; Myobudani, H; Yamamoto, N
Abstract: Background: VEGF and Ang2 signaling have key functions in tumor angiogenesis and have an immunosuppressive effect in the tumor microenvironment. Preclinical data show that combined inhibition of VEGF/Ang2 and PD-1 enhances the tumor microenvironment to support T-cell mediated destruction of tumor cells. BI 836880 is a humanized bispecific nanobody that targets VEGF and Ang2, and BI 754091 is an anti-PD-1 antibody. Each have shown safety and preliminary activity as monotherapy in phase I (recommended phase 2 dose [RP2D] 720 mg intravenous [iv] every 3 weeks [q3w] for BI 836880 [Caucasian pts] and 240 mg iv q3w for BI 754091 [Caucasian and Japanese pts]). An ongoing phase Ib study (NCT03468426) will determine the RP2D, safety and preliminary activity of BI 836880 + BI 754091 in Caucasian pts. The current phase I study will determine the maximum tolerated dose (MTD)/RP2D of BI 836880 alone or in combination with BI 754091 in Japanese pts with advanced solid tumors. Trial design: This open-label, multi-center, dose-escalation trial will enroll pts with a confirmed diagnosis of advanced, unresectable and/or metastatic solid tumors (any type) whose disease is not amenable to standard therapies or where there is no therapy of proven efficacy. Pts are required to have an ECOG PS ≤ 1 and adequate organ function. The study has 2 parts: Part 1 will assess BI 836880 monotherapy and Part 2 will assess BI 836880 + BI 754091. Pts will receive BI 836880 at a starting dose of 360 mg iv q3w in Part 1 and of 120 mg iv q3w in Part 2 (in combination with BI 754091 240 mg iv q3w). Administration will continue until progressive disease, unacceptable toxicity or other withdrawal criteria. Dose escalation will be guided by Bayesian logistic regression models with overdose control in both Parts, with oversight from a safety monitoring committee. Primary endpoint is MTD/RP2D of BI 836880 alone (Part 1) and in combination with BI 754091 (Part 2). Secondary/further endpoints will document the safety, pharmacokinetics, anti-tumor activity and immunogenic response of BI 836880 alone and in combination with BI 754091. It is planned to enroll 24 pts. Clinical trial identification: NCT03972150. Legal entity responsible for the study: Boehringer Ingelheim. Funding: Boehringer Ingelheim. Disclosure: K. Yamazaki: Speaker Bureau / Expert testimony: Chugai; Speaker Bureau / Expert testimony: Takeda; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Taiho; Speaker Bureau / Expert testimony: Yakult; Speaker Bureau / Expert testimony: Ono; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Lily; Speaker Bureau / Expert testimony: Sanofi; Speaker Bureau / Expert testimony: Bayer; Speaker Bureau / Expert testimony: Merck-Serono; Speaker Bureau / Expert testimony: MSD; Speaker Bureau / Expert testimony: Bristol-Myers Squibb. T. Shimizu: Honoraria (self): Clinical Research Joint Scientific Committee Review Member for Phase 1 trials in Hong Kong; Honoraria (self): HKSAR China ; Advisory / Consultancy, Research grant / Funding (institution): Takeda Oncology; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Eli Lilly; Research grant / Funding (institution): Daiichi-Sankyo; Research grant / Funding (institution): Bristol-Myers Squibb; Research grant / Funding (institution): Eisai; Research grant / Funding (institution): Incyte; Research grant / Funding (institution): Astellas; Research grant / Funding (institution): Chordia Therapeutics; Research grant / Funding (institution): 3D-Medicine; Research grant / Funding (institution): Symbio Pharmaceuticals; Research grant / Funding (institution): PharmaMar; Research grant / Funding (institution): Five Prime; Research grant / Funding (institution): AstraZeneca ; Research grant / Funding (institution): AbbVie. T. Takahashi: Honoraria (self), Research grant / Funding (institution): AstraZeneca KK; Honoraria (self), Research grant / Funding (institution): Chugai Pharmaceutical Co., Ltd.; Honoraria (self), Research grant / Funding (institution): Eli Lilly Japan K.K.; Honoraria (self), Research grant / Funding (institution): Ono Pharmaceutical Co., Ltd.; Honoraria (self), Research grant / Funding (institution): MSD K.K.; Honoraria (self), Research grant / Funding (institution): Boehringer Ingelheim Japan, INC; Honoraria (self): Roche Diagnostics K.K.; Research grant / Funding (institution): Pfizer Japan Inc. Y. Tanaka: Full / Part-time employment: Boehringer Ingelheim. H. Myobudani: Full / Part-time employment: Boehringer Ingelheim. N. Yamamoto: Advisory / Consultancy, Research grant / Funding (institution): Eisai; Advisory / Consultancy, Research grant / Funding (institution): Takeda; Advisory / Consultancy: Otsuka; Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim; Advisory / Consultancy: Cimic; Advisory / Consultancy, Research grant / Funding (institution): Chugai; Speaker Bureau / Expert testimony, Research grant / Funding (institution): BMS; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Pfizer; Speaker Bureau / Expert testimony: AstraZeneca; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Eli Lilly; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Ono; Speaker Bureau / Expert testimony: Sysmex; Research grant / Funding (institution): Astellas; Research grant / Funding (institution): Taiho; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): Daiichi-Sankyo; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Kyowa-Hakko Kirin; Research grant / Funding (institution): Janssen Pharma; Research grant / Funding (institution): MSD; Research grant / Funding (institution): Merck. All other authors have declared no conflicts of interest.